The first species of the Cis vitulus species-group (Coleoptera: Ciidae) from Brazil - Rosa-Oliveira, Ayessa; Borlini, Paula Vieira; Souza-Gonçalves, Igor (Zootaxa, 2026)
Cis cris sp. nov. is described based on specimens collected in Paulista, Pernambuco, in the Northeast Region of Brazil. It is the first species of the Cis vitulus species-group recorded from Brazil. We provide a detailed description and images of both male and female, including their terminalia.